PENGAWASAN DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA TERHADAP PERPARKIRAN DI KOTA PEKANBARU (Studi Kasus Kecamatan Sukajadi 2014) - Asep Rezapahlepi; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
management is a social phenomenon in the city of Pekanbaru which is in dire need of government attention If the management of parking is not supervised properly then it is certain the government will be difficult to make the arrangement of the city and the problems that occur will affect the unstable reception area were obtained from the parking sector itself Organizers and Management Perparkiran Pekanbaru City area under Regulation No. 3 of 2005 on Amendment Pekanbaru City Regional Regulation No. 14 Year 2001 on the Implementation and Management Perparkiran is the Department of Transportation, Communications, and Information Technology. Here are the phenomena that occur in the parking that occurred in the District Sukajadi Found occurrence of fluctuating revenues parking fees on public roads, caused by parking attendants who are not depositing evidence or parking ticket to the Department of Transportation, No cooperation contract between managers with executive parking as specified in Local Regulation, Karna no cooperation contract, the impact on the irregular implementation of management including the implementation of the field by the parking attendant, triggering disorder vehicular traffic, is still a parking attendant who did not give tickets to the public parking that impact the proceeds from the public parking fees. This research is a descriptive study, in which the author presents and describes how to control the transportation bureau and informati on parking in the city of Pekanbaru a case study in District Sukajadi. And to know the factors that affect the parking supervision. The technique of collecting data is to interview and the key informant is a team of surveillance, parking attendants and community leaders. Results of the study found that the supervision has not been done optimally This is because the weakness of the sanctions provided for parking attendants were violated and the number of supervisors who lack the resulting lack of supervision performed so many illegal parking. As for some of the factors that affect the implementation of parking control in the city of Pekanbaru is a human resources (HR) as quality inspectors and the number of supervisory personnel in the field, limited funds to conduct surveillance and a lack of community participation factor against parking in the district Sukajadi.Keywords: monitoring, setting standards, corrective actions